Mutual Intercultural Perception: How Does It Affect Technical Communication? Some Data from China, the Netherlands, Germany, France, and Italy - ULIJN, JAN M. and ST.AMANT, KIRK (Technical Communication, 2000)
◆ Investigates how individuals from different cultures perceive questioning and pausing/interrupting behavior ◆ Demonstrates that culture can affect how different individuals perceive and interpret the same situation
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80Mzc0ODg1NQ